Total or Partial Knee Arthroplasty Trial - TOPKAT: study protocol for a randomised controlled trial. - Beard, D; Price, A; Cook, J; Fitzpatrick, R; Carr, A; Campbell, M; Doll, H; Campbell, H; Arden, N; Cooper, C; Davies, L; Murray, D (BioMed Central, 2013)
BACKGROUND: In the majority of patients with osteoarthritis of the knee the disease originates in the medial compartment. There are two fundamentally different approaches to knee replacement for patients with unicompartmental disease: some surgeons feel that it is always best to replace both the knee compartments with a total knee replacement (TKR); whereas others feel it is best to replace just the damaged component of the knee using a partial or unicompartment replacement (UKR). Both interventions are established and well-documented procedures. Little evidence exists to prove the clinical and cost-effectiveness of either management option. This provides an explanation for the high variation in treatment of choice by individual surgeons for the same knee pathology.The aim of the TOPKAT study will be to assess the clinical and cost effectiveness of TKRs compared to UKRs in patients with medial compartment osteoarthritis. METHODS/DESIGN: The design of the study is a single layer multicentre superiority type randomised controlled trial of unilateral knee replacement patients. Blinding will not be possible as the surgical scars for each procedure differ.We aim to recruit 500 patients from approximately 28 secondary care orthopaedic units from across the UK including district general and teaching hospitals. Participants will be randomised to either UKR or TKR. Randomisation will occur using a web-based randomisation system. The study is pragmatic in terms of implant selection for the knee replacement operation. Participants will be followed up for 5 years. The primary outcome is the Oxford Knee Score, which will be collected via questionnaires at 2 months, 1 year and then annually to 5 years. Secondary outcomes will include cost-effectiveness, patient satisfaction and complications data. TRIAL REGISTRATION: Current Controlled Trials ISRCTN03013488; ClinicalTrials.gov Identifier: NCT01352247.